Do tarantulas have teeth? : questions and answers about poisonous creatures - Berger, Melvin; Berger, Gilda; Effler, James M., 1956- (New York, N.Y. : Scholastic Reference, 2000)
Provides answers to a variety of questions about various poisonous creatures, such as "Do Gila monsters bite humans," "What are killer bees," "Which ant sting hurts the most," and "Are frogs poisonous?"
G5
Keywords: Poisonous animals -- Miscellanea -- Juvenile literature; Poisonous animals -- Miscellanea; Questions and answers